2022
DOI: 10.1039/d2ob00367h
|View full text |Cite
|
Sign up to set email alerts
|

A cationic AIEgen and hexametaphosphate based simple and convenient fluorometric assay for alkaline phosphatase and its inhibitor

Abstract: Alkaline phosphatase (ALP) is an important biomarker to diagnose a number of diseased conditions, such as, anaemia, hepatobiliary diseases, chronic nephritis, and hypothyroidism. Therefore, the development of simple and convenient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…By using AIE and ACQ phenomenon, our group reported various TPE-based sensors for cations [20] and anions [21,22] as well as for alkaline phosphatase. [23] Herein, we have reported 4,4',4'',4'''-(ethene-1,1,2,2tetrayl)tetrakis(N,N-dimethylaniline) (TPE-DMA) for the detection of explosive nitroaromatic compounds, such as 2, 4, 6trinitrophenol/picric acid (PA), 2, 4-dinitrophenol (DNP) and pnitrophenol (NP) over other nitro compounds along with phenol in CHCl 3 . The probe TPE-DMA is highly selective and sensitive towards nitro explosives especially PA, in the presence of various metal cations and anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using AIE and ACQ phenomenon, our group reported various TPE-based sensors for cations [20] and anions [21,22] as well as for alkaline phosphatase. [23] Herein, we have reported 4,4',4'',4'''-(ethene-1,1,2,2tetrayl)tetrakis(N,N-dimethylaniline) (TPE-DMA) for the detection of explosive nitroaromatic compounds, such as 2, 4, 6trinitrophenol/picric acid (PA), 2, 4-dinitrophenol (DNP) and pnitrophenol (NP) over other nitro compounds along with phenol in CHCl 3 . The probe TPE-DMA is highly selective and sensitive towards nitro explosives especially PA, in the presence of various metal cations and anions.…”
Section: Introductionmentioning
confidence: 99%
“…Tang and co‐workers introduced the aggregation‐induced emission (AIE) [18] in 2001 while Förster and Kasper discovered the aggregation‐caused quenching (ACQ) [19] phenomenon in 1955. By using AIE and ACQ phenomenon, our group reported various TPE‐based sensors for cations [20] and anions [21,22] as well as for alkaline phosphatase [23] …”
Section: Introductionmentioning
confidence: 99%
“…By tuning such receptor sites on phenyl rings, our group has reported an AIE-active tetrapyridyl-substituted TPE (TPy-TPE) for intracellular pH detection 21 and zinc sulfate sensing. 22 Nevertheless, our group also reported various probes for the selective detection of toxic anions, 23,24 cations, 25,26 biomolecules, 27 and explosive sensors. 28 The reported molecule, tetrakis(4-(dimethylamino)phenyl)ethylene, is already known in the literature; Qi et al reported the mechanochromic and polymorphic emission of this molecule, 29 and our group also reported this molecule for the detection of explosive nitroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%